Qingchang Wenzhong Decoction Accelerates Intestinal Mucosal Healing Through Modulation of Dysregulated Gut Microbiome, Intestinal Barrier and Immune Responses in Mice - Sun, Zhongmei; Li, Junxiang; Wang, Wenting; Liu, Yuyue; Liu, Jia; Jiang, Hui; Lu, Qiongqiong; Ding, Panghua; Shi, Rui; Zhao, Xingjie; Yuan, Wenjing; Tan, Xiang; et al. (Frontiers in Pharmacology, 2021)
Inflammatory bowel disease (IBD), a group of multifactorial and inflammatory infirmities, is closely associated with dysregulation of gut microbiota and host metabolome, but effective treatments are currently limited. Qingchang Wenzhong Decoction (QCWZD) is an effective and classical traditional herbal prescription for the treatment of IBD and has been proved to attenuate intestinal inflammation in a model of acute colitis. However, the role of QCWZD in recovery phase of colitis is unclear. Here, we demonstrated that mice treated with QCWZD showed a faster recovery from dextran sulfate sodium (DSS)-induced epithelial injury, accompanied by reduced mucosal inflammation and attenuated intestinal dysbiosis using bacterial 16S rRNA amplicon sequencing compared to those receiving sterile water. The protective effects of QCWZD are gut microbiota dependent, as demonstrated by fecal microbiome transplantation and antibiotics treatment. Gut microbes transferred from QCWZD-treated mice displayed a similar role in mucosal protection and epithelial regeneration as QCWZD on colitis in mice, and depletion of the gut microbiota through antibiotics treatments diminished the beneficial effects of QCWZD on colitis mice. Moreover, metabolomic analysis revealed metabolic profiles alternations in response to the gut microbiota reprogrammed by QCWZD intervention, especially enhanced tryptophan metabolism, which may further accelerate intestinal stem cells-mediated epithelial regeneration to protect the integrity of intestinal mucosa through activation of Wnt/β-catenin signals. Collectively, our results suggested that orally administrated QCWZD accelerates intestinal mucosal healing through the modulation of dysregulated gut microbiota and metabolism, thus regulating intestinal stem cells-mediated epithelial proliferation, and hold promise for novel microbial-based therapies in the treatment of IBD.